Genome-wide identification and characterization of PIN-FORMED (PIN)and PIN-LIKES (PILS)gene family reveals their role in adventitious root development in tea nodal cutting (Camellia sinensis) - Hu, S.; Liu, X.; Xuan, W.; Mei, H.; Li, J.; Chen, X.; Li, X. H.
Auxin affects all aspects of plant growth and development, including morphogenesis and adaptive responses. Auxin transmembrane transport is promoted by PIN formation (PIN)and a structurally similar PIN-like (PILS)gene family, which jointly controls the directional transport of the auxin between plant cells, and the accumulation of intracellular auxin. At present, there is no study investigating the roles of CslPIN and CslPILS gene family in root development in the tea plant (Camellia sinensis). In this study, 8 CslPIN and 10 CslPILS genes were identified in the tea plant, and their evolutionary relationships, physical and chemical properties, conserved motifs, cis-acting elements, chromosome location, collinearity, and expression characteristics were analyzed. The mechanism of CslPIN and CslPILS in the formation of tea adventitious roots (ARs)was studied by the AR induction system. Through functional verification, the regulation of CslPIN3 gene on root growth and development of tea plant was studied by over-expression of CslPIN3 in Arabidopsis thaliana and in situ hybridization in Camellia sinensis. The results confirmed CslPIN3 was involved in the regulation of root growth and development as well as auxin accumulation. This study provides a better insight into the regulatory mechanism of CslPIN and CslPILS gene family on the formation of AR in tea plant.
Keywords: CAMELLIA SINENSIS; AUXIN; PIN AND PILS; ADVENTITIOUS ROOT FORMATION; CSLPIN3